Unusual Case of Life-Threatening Gastro Intestinal Bleed from a Splenic Artery Pseudoaneurysm: Case Report and Review of Literature - Puneet Menaria; Venkata Muddana (Case Reports in Gastrointestinal Medicine)
Large upper gastro intestinal (GI) bleeding can be life-threatening. Splenic artery pseudoaenurysm (SAP) is rare but can cause massive upper GI bleeding. We report a case of a 57-year-old woman who had massive upper GI bleeding from SAP eroding into distal duodenum. Literature review shows SAP can bleed into stomach or pancreatic pseudocyst or biliary tree and peritoneal cavity; however, there are no previous reported cases of SAP bleeding into distal duodenum. Splenic artery embolization (SAE) is the preferred treatment for a bleeding SAP. Splenic infarcts can result following a SAE.